Baseline atmospheric corrosion in the Geothermal Plant Las Pailas, Guanacaste, Costa Rica. (UNED Research Journal, 2015)
During the construction of the Las Pailas geothermal plant, atmospheric corrosion was evaluated for 5 years. Atmospheric monitoring and gravimetric analysis with low alloy steel (ASTM A36), were done according to ISO 9223 and its associated procedure. There were low values of pollution by chlorides and sulfates, around 5 mg m-2 día-1 and without important levels of acid rain, despite the proximity of an active volcano, which indicates an atmosphere of “rural type”. TDH’s level was 60 %, initial corrosion speed was 40 μm year-1, and this estabilized after 3 years in 20 µm year-1, with protective oxides. The accumulated corrosion estimated by the model meet ISO Corroag of ISO 9226. The Matlab model produced a best adjustment exponential model with a time dependence factor of 0,89.
Keywords: Atmospheric corrosion; steel ASTM A36; ISO 9223; ISO 9224; ISO 9225 and ISO 9226.